CONCEPTS OF RELIGION AND RELIGIOUS FLOWS (Study of Epistemology and Theory of Religion and the Heresy of the Shia sect) In the view of Islam Ahlu Sunnah wal Jama'ah) - Muhammad Khairan Arif (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2022)
This paper aims to explain and explain the concept and position of religion in human life, that religion is belief and submission to the teachings of Allah and His Messenger, so that religion is different from other cultures, organizations and human creations. Religion must have a standard of truth that is recognized and agreed upon by consensus, in order to be safe from fraud and misdirection. This paper also explains and exposes the heresies of sects and sects in Islam according to the standards and scales of the Qur'an, A-Sunnah and the views of the Companions ra. So that Muslims are protected from the misguidance of these religious sects. The method of writing this paper uses descriptive, historical and comparative methods with a study approach to classical and modern Islamic literates, then compares them with the reality of the context of religion and diversity in the lives of Muslims today. Paper ini bertujuan menjelaskan dan memaparkan konsep dan posisi agama dalam kehidupan manusia, bahwa agama adalah keyakinan dan ketundukkan pada ajaran-ajaran Allah dan RasulNya, sehingga agama berbeda dengan budaya, organiasi dan ciptaan manusia lainya. Agama harus memiliki standar kebenaran yang diakui dan disepakati secara consensus, agar selamat dari penyelewengan dan penyesatan. Paper ini juga menjelaskan dan menyingkap kesesatan sekte-sekte dan aliran-aliran dalam Islam sesuai standar dan timbangan Al-Qur’an, A-Sunnah serta pandangan Para Sahabat ra. Sehingga umat Islam terhindar dari kesesatan aliran-aliran keagamaan tersebut. Metode penulisan paper ini menggunakan metode Deskriptif, Historis dan Komparatif dengan pendekatan studi terhadap literatus-literatus Islam Klasik dan modern, kemudian menkomparasikannya dengan realitas konteks agama dan keberagamaan dalam kehidupan umat Islam saat ini